مادہ منویہ اور مصنوعی حمل کے بینک : تعارف ، ارتقا اور شرعی حکمSperm & Artificial Insemination Banks: Introduction, Evolution & Shariah Ruling (Al-Qamar, 2021)
Having children is a natural desire of all human beings, which is why the Prophets have expressed this desire to Allah even in old age. Allah Almighty has established a natural way of mating between man and woman for the fulfillment of this desire and the attainment of this, He has prescribed a pure and lasting relationship like marriage. And with that, it has also been said that having children is a blessing and grace from Allah۔ With the advancement of modern science, man has been able to adopt artificial insemination through modern medical procedures rather than natural methods. The first test-tube baby was born in 1978 in Manchester. Although man has gained tremendous success in this field, there are many imperfections in adopting this method according to Islamic and medical science which are not only harmful to mother and child but also leave a negative impact on the moral values of the society. This article will highlight the medical, social, and moral problems in adopting such scientific methods of having children. The study will provide an in-depth analysis of Islamic ruling for adopting this method and suggest a guideline for the Muslim community to follow.
Keywords: Sperm; Artificial insemination; Test Tube Baby; Infertility; Sterility; Laparoscopy; Islamic Ruling